PaloPro: a platform for knowledge extraction from big social data and the news. (2017) - Makrynioti, Nantia; Grivas, Andreas; Sardianos, Christos; Tsirakis, Nikos; Varlamis, Iraklis; Vassalos, Vasilis; Poulopoulos, Vassilis; Tsantilas, Panagiotis
PaloPro is a platform that aggregates textual content from social media and news sites in different languages, analyses them using a series of text mining algorithms and provides advanced analytics to journalists and social media marketers. The platform capitalises on the abundance of social media sources and the information they provide for persons, products and events. In order to handle huge amounts of multilingual data that are collected continuously, we have adopted language independent techniques at all levels and from an engineering point of view, we have designed a system that takes advantage of parallel distributed computing technologies and cloud infrastructure. Different systems handle data aggregation, data processing and knowledge extraction and others deal with the integration and visualisation of knowledge. In this paper, we focus on two important text mining tasks, named entity recognition from texts and sentiment analysis to extract the sentiment associated with the corresponding identified entities.